2019
DOI: 10.1111/sji.12738
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody against human Tim‐3 enhances antiviral immune response

Abstract: T cell immunoglobulin and mucin domain protein 3 (Tim‐3) is an immune checkpoint inhibitor in T cells and innate immune cells. The deregulated upregulation of Tim‐3 is related to immune exhaustion in tumour and viral infection. To overcome Tim‐3‐mediated immune tolerance, we developed a novel monoclonal antibody against human Tim‐3 (L3G) and investigated its roles in inhibiting Tim‐3 signalling and overcoming immune tolerance in T cells and monocytes/macrophages. The administration of L3G to cultured periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Interestingly, recent work also confirmed that exhausted T cells are existent in acute viral infections, and T cells from patients in the acute phase of Ebola infection manifested with enhancing PD-1 expression but impaired IFN-γ production [23]. Moreover, blocking Tim-3 signal efficiently enhanced IFN-γ secretion from T cells following H1N1 infection model [24]. Our previous work has firstly reported that SARS-CoV-2 triggers the expression of PD-1 and Tim-3 on T cells, suggesting exhausted T cells were persistent in COVID-19 patients during SARS-CoV-2 acute infection [7].…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, recent work also confirmed that exhausted T cells are existent in acute viral infections, and T cells from patients in the acute phase of Ebola infection manifested with enhancing PD-1 expression but impaired IFN-γ production [23]. Moreover, blocking Tim-3 signal efficiently enhanced IFN-γ secretion from T cells following H1N1 infection model [24]. Our previous work has firstly reported that SARS-CoV-2 triggers the expression of PD-1 and Tim-3 on T cells, suggesting exhausted T cells were persistent in COVID-19 patients during SARS-CoV-2 acute infection [7].…”
Section: Discussionmentioning
confidence: 83%
“…TIM3 has emerged as a promising target for tumor immunotherapy, and a few antibodies against TIM3 have been reported to exhibit excellent effects in enhancing antiviral immune responses, stimulating IFN-mediated anti-tumor immunity of T cells, and counteracting tumor growth [ 27 ]. Also, there are some reports on TIM3 inhibitors, but mechanisms of the action are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Surface expressed Tim‐3 on macrophages naturally mediates inhibitory signals after binding to its ligands. In this study, sTim‐3 was used to competitively inhibit the interaction between membrane Tim‐3 and its ligands 37,38,42 . We first examined the effects of Tim‐3 on the metabolic reprogramming of macrophages.…”
Section: Discussionmentioning
confidence: 99%